STUDY OF THE PERFORMANCE OF THE DYNAMIC LEVEL STABILIZATION SYSTEM OPERATION IN THE WELLBORE EQUIPPED WITH AN ELECTRICAL SUBMERSIBLE PUMP UNIT - Alexander S. Totanov; Veronika A. Molchanova; Kamil R. Urazakov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Link for citation: Totanov A.S., Molchanova V.A., Urazakov K.R. Study of the performance of the dynamic level stabilization system operation in the wellbore equipped with an electrical submersible pump unit. Bulletin of the Tomsk Polytechnic University. Geo Аssets Engineering, 2023, vol. 334, no. 8, рр. 210-219. In Rus.